Bottom-Up Strategy in Teaching Listening for Academic Purposes for EFL in Pesantren-Based University - Aries Fachriza; Naajihah Mafruudloh; Dinar Dipta; Diska Fatima Virgiyanti; Eka Indah Nuraini; Eta Lica Hanan Nadifa (Journal of Foreign Language Teaching and Learning, 2022)
Receiving information begins with listening. EFL learners at universities should master listening for academic purposes with appropriate strategies. This article examined the strength of the bottom-up strategy in teaching listening for the academic purpose of the third-semester female students in the Department of English Language Education, the University of Darussalam Gontor, which is a pesantren -based university. This research utilized a quasi-experimental with one group pretest-posttest design. The participants involved 14 who were regarded in English language teaching.  They were tested by pre-and post-treatment listening for academic purposes. The data were analyzed by paired sample t-test. The results showed a significant inequality between the mean score of the pre-test and post-test. The mean score of the post-test of learners was improved than theirs in the pre-test. Thus, the female learners in this research achieved well in promoting teaching listening for academic purposes after being treated using a bottom-up strategy.